Pembuatan Beton Berbasis OPC Dengan Penambahan Turbulence Assisted Shear Exfoliation (TASE) Graphene - Febri Riandi; Amun Amri; Evelyn Evelyn (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Concrete is the primary raw material for construction which consists of constituent materials in the form of portland cement, fine aggregate, coarse aggregate, water and with or without added materials. Graphene is a nano-sized and strong material. The use of graphene can be used as an additive (admixture or additive) to improve the quality and quality of concrete. This research aims to make concrete based on Ordinary Portland Cement (OPC) with the addition of graphene nanosheets (GNS), as well as to study the effect of increasing the number of graphene nanosheets (GNS) and differences in sand size on the mechanical properties and morphology of the resulting concrete. Concrete manufacture begins with preparing a graphene solution which is made by synthesizing pure graphite through the TASE method. Then the concrete is made by mixing all the materials to be used manually with the ratio of raw materials (cement: sand: gravel: water) is 1: 2: 3: 0.6 until homogeneous. The results of testing the mechanical properties of concrete show that the highest compressive strength is 21.75 MPa obtained from variations in the addition of 5% graphene with sand size gradations, namely mix (200 <x <100 with 100 <x12), the lowest porosity and water absorption is 9% and 3.94% was obtained from the variation of 5% graphene addition with sand size gradations, namely mix (200 <x <100 with 100 <x12), while the SEM analysis results showed that the higher the addition of graphene to the concrete matrix can reduce the porosity value of the concrete so that can improve the mechanical properties of concrete. Keywords: concrete, geopolymer, graphene, OPC, TASE